Postgraduate Learning Innovation in the Age of Artificial Intelligence - Murtono; Mulyo Prayitno (Advances Educational Innovation, 2025)
Objective: To explore how artificial intelligence (AI) can act as a moderator in supporting learning effectiveness at the postgraduate level through traditional educational elements such as teaching strategies, curriculum development, digital literacy, and learner engagement.Methods: Data were collected via a structured quantitative survey from 140 postgraduate students selected purposively. Pearson correlation and multiple regression with moderation analysis were used to determine the interaction effects of AI on learning effectiveness based on the data gathered.Results: Results show the crucial moderating effect of AI on the impact of digital competence and teaching practice to learning outcomes. Although conventional academic variables that influence the learning effectiveness exert their effects, their effects are amplified when AI is incorporated into the instructional practices and digital platforms. AI improves feedback mechanisms, enables interactivity, and strengths individualized learning paths.Novelty: While past literature utilized AI as an independent or mediating variable, we view AI as a moderator, namely, an enabling mechanism that enhances already existing educational mechanisms rather than replicating them in a different way. Such a nuanced role is indicative of a paradigm shift in postgraduate higher education technology adoption.Theory and Policy Implications: This study extends both constructivist and cognitive load theories showing how AI can ease cognitive burden but at the same time enhance knowledge construction. The results propose strategies for policymakers to incorporate AI in postgraduate curricula to build self-adaptive, data-driven, and student centered learning environments.